The complete chloroplast genome sequence of Solanum hougasii, one of the potato wild relative species. Issue 2 (3rd July 2018) - Cho, Kwang-Soo; Cho, Ji-Hong; Im, Ju-Sung; Choi, Jang-Gyu; Park, Young-Eun; Jang, Dong-Chil; Hong, Su-Young; Park, Tae-Ho
Abstract: Solanum hougasii is a wild tuber-bearing species belonging to the family Solanaceae. The complete chloroplast genome of S. hougasii was constituted by de novo assembly, using a small amount of whole genome sequencing data. The chloroplast genome of S. hougasii was a circular DNA molecule with a length of 155, 549 bp and consisted of 85, 990 bp of large single copy, 18, 373 bp of small single copy, and 25, 593 bp of a pair of inverted repeat regions. A total of 158 genes were annotated, including 105 protein-coding genes, 45 tRNA genes, and eight rRNA genes. Maximum likelihood phylogenetic analysis with 25 Solanaceae species revealed that S. hougasii is most closely grouped with S. tuberosum .